NUCLEAR FACTOR KAPPA B AS A POTENTIAL TARGET FOR PHARMACOLOGICAL CORRECTION ENDOTHELIUM-ASSOCIATED PATHOLOGY - Vera Ragulina; Darya Kostina; Anton Dovgan; Yuriy Burda; Sergey V. Nadezhdin (Belgorod National Research University, 2017)
The nuclear factor kappa B (NF-κB) is one of transcription factors. A high interest in studying the biological role of the signal system and its contribution to the development of cardiovascular, oncological and autoimmune diseases is obvious. A number of stimuli (pro-inflammatory cytokines: tumor necrosis factor α, interleukin 1β, ligand CD40 and others) trigger the canonical and non-canonical pathways of NF-κB signaling, which increase the expression of genes regulating synthesis of cytokines and chemokines, cell proliferation and differentiation, angiogenesis, immune reactions and apoptosis. However, pathological activation of NF-κB violates the balance of substances participating in the normal activity of the cardiovascular system. This leads to the development and progression of endothelium-associated pathology and comorbidity. Contribution of pathological activation the NF-κB signaling system in the formation of vicious circles in atherosclerosis, coronary heart disease, pulmonary hypertension, ischemic-reperfusion injury, is not subject to doubt. Thus, the search for new therapeutic targets and strategies for modulating the activity of the NF-κB signaling pathway is one of the key strategies for the development of experimental pharmacology. Another important aspect of studying the pharmacological activity of NF-κB activity modulators is the choice of a valid and easily reproducible way of assessing the activity of this system.